Information modelling and knowledge bases XXI - European-Japanese Conference on Information Modelling and Knowledge Bases 2009); Welzer, Tatjana, 1961-; IOS Press (Amsterdam : IOS Press, 2010)
Drawing together researchers and practitioners from the field, European-Japanese conferences aim to advance research into, and the application of, information modelling and knowledge bases. This title contains papers presented at the 19th European-Japanese Conference on information modelling and knowledge bases (EJC 2009).
Title page; Preface; Programme Committee; Contents; The 4D World Map System with Semantic and Spatiotemporal Analyzers; Analysis and Description System for Children's Inquiry in a Multimedia Science Learning Environment; From Word Form Surfaces to Communication; Detection of Difference Between News Articles on the Same Topic Based on Sequential Comparison; Context-Based Knowledge Creation and Sharing in Cross-Cultural Collaborative Communities; Knowledge Management in Service-Oriented Systems; Concept Drift in Documents and Formal Concept Analysis.
Print version record.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Information modeling -- Congresses; System design -- Congresses; Expert systems (Computer science) -- Congresses; Modèles d'information -- Congrès.; Conception de systèmes -- Congrès.; Systèmes experts (Informatique) -- Congrès.; Expert systems (Computer science); Information modeling; System design; Conference papers and proceedings